?STUDIES ON STORAGE OF POTATO TUBERS WITH SPECIAL REFERENCE TO SWEETENING PROCESS - KHAN, NAWAB; ZAMAN, RASHIDA; EHTESHAMUDDIN, A. F. M. (Biological Sciences - PJSIR, 1994)
Effect of storage temperatures and chemical treatments on accumulation of sugars in potato tubers during storage was studies. At regular intervals throughout the storage period, samples were analysed for reducing and non-reducing sugars. Storage at low temperature (4_5') resulted in accumulation of more reducing and non-reducing sugars than storage at 12-14'. Whereas reducing sugar increased rapidly during storage at low temperature, rapid increase inreducing sugar was observed after about 2 months in tubers stored at 12-14'. Treatment with sodium acetate solution proved very effective in retarding the sweetening process. Accumulation of sugar in sodium acetate treated tubers was 50% less than in untreated samples. Treatments with sodium meta sulphite, potassium sorbate and hydrogen peroxide were not as effective in reducing the sweetening process.